Artificial Intelligence and its Impact on Attracting Talent to Human Resources - Karim Sayhood Karam (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the pivotal role of artificial intelligence (AI) in talent attraction within the human resources sector, particularly in the context of modern technological advancements. We aim to understand the influence of AI on recruitment processes and identify factors affecting talent attraction in the information age, as well as the associated challenges. The study focuses on how AI impacts recruitment and utilizes statistical methods, including interviews, questionnaires, standard deviation, arithmetic mean, and Spearman's rank correlation, to achieve accurate results. Participants included 100 employees and professors from the Ministry of Higher Education and Scientific Research, with a research community of around 750. Findings suggest that organizations employing AI for recruiting, attracting, training, and guiding individuals tend to succeed. The study recommends the urgent integration of AI into organizational operations, urging a shift from traditional applicant comparison methods to modern assessment techniques while avoiding favoritism. Additionally, organizations should implement contemporary training programs to boost employee performance.